2019
DOI: 10.1111/asj.13266
|View full text |Cite
|
Sign up to set email alerts
|

Adding heat‐treated rapeseed to the diet of yak improves growth performance and tenderness and nutritional quality of the meat

Abstract: Heat‐treated rapeseed was supplemented to indoor fed yaks in winter to test the effect on dry matter intake (DMI), body mass change, and meat quality. Sixteen 3‐year‐old yak steers (124 ± 15.3 kg) were divided randomly into two groups and were offered either heat‐treated rapeseed (HTR) or rapeseed meal (CONT). The yaks were allowed 14 days for adjustment and measurements were made over 120 d. There was no difference in DMI between groups (p = 0.67), but average daily gain tended to be higher (p < 0.056) and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
1
14
1
Order By: Relevance
“…They are raised between 3000 and 5000 m above sea level and are well adapted to the harsh conditions of the QTP. Yaks provide meat [ 2 ] and milk [ 3 , 4 ] for food, dung for fuel, and wool for clothes [ 5 ], and they serve as a cultural symbol for Tibetans [ 6 ]. They are also important in maintaining stability of the alpine ecosystem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are raised between 3000 and 5000 m above sea level and are well adapted to the harsh conditions of the QTP. Yaks provide meat [ 2 ] and milk [ 3 , 4 ] for food, dung for fuel, and wool for clothes [ 5 ], and they serve as a cultural symbol for Tibetans [ 6 ]. They are also important in maintaining stability of the alpine ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the meat and the milk of yak are of better quality and have higher protein content and polyunsaturated fatty acid concentrations than cattle from the lowland, for example, Holstein cattle [ 2 , 3 ]. However, meat and milk production in yaks is low.…”
Section: Introductionmentioning
confidence: 99%
“…Heat treatment of meat has also been demonstrated to denature and solubilize connective tissues such as collagen (Li, Wang, Xu, Gao, & Zhou, 2013; Dong et al, 2018). However, heat treatment of meat can also cause hardening of myofibrillar proteins due to heat denaturation and severe moisture loss from prolonged cooking (Chumngoen, Chen, & Tan, 2017; Hao et al, 2019). Hence, alternative methods of meat tenderization that can provide the best meat quality for customer satisfaction is sought, and the most popular treatment method is using a proteolytic enzyme called protease (Ermis, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Heat treatment of meat has also been demonstrated to denature and solubilize connective tissues such as collagen (Li, Wang, Xu, Gao, & Zhou, 2013;Dong et al, 2018). However, heat treatment of meat can also cause hardening of myofibrillar proteins due to heat denaturation and severe moisture loss from prolonged cooking (Chumngoen, Chen, & Tan, 2017;Hao et al, 2019).…”
mentioning
confidence: 99%
“…However, in some systems, modern management practices have introduced dietary supplements to yaks, especially during the winter period to reduce the loss of body mass and to improve growth performance. In an earlier study, we reported that the feed to gain ratio was improved in yaks offered heat‐treated traditional rapeseed ( Brassica napus ) (Hao et al., 2019). Traditional rapeseed contains 25%–45% erucic acid in the oil and 50–100 μmol/g glucosinolates in the meal, anti‐nutritional factors that are detrimental to the health and performance of the animal (Heuzé et al., 2020; Rymer & Short, 2002).…”
Section: Introductionmentioning
confidence: 99%